Digital Videos in Financial Accounting: A Sociocognitive Approach to Learning - Broadley, Tania; Taylor, Grantley (Common Ground, 2013)
Understanding the important concepts necessary to undertake the preparation of consolidated financial statements has proven challenging for many accounting undergraduate students. As a result, the development of multimedia modelling concepts such as acquisition analysis, business combination valuation entries, reacquisition entries and intragroup transactions were embedded within an e-learning environment. The principle of modelling, derived from social cognitive theory, was applied to the design of the multimedia. A study was conducted to gauge the effectiveness of the approach and consider student perceptions with regard to learning through this approach. Quantitative data were collected from accounting undergraduate students (n= 464) enrolled across three different cohorts including international campuses (n=386), an Australian campus (n=49) and a distance education cohort (n=29). Analyses were undertaken to show significant differences between these cohorts. This research paper presents findings that indicate a positive and significant association between the number of times the videos were accessed, and the assignment score (p<0.05) was evident, suggesting that students that referred to the videos relatively frequently were able to utilise the knowledge gained from the videos to assist them in completing the assignment.